Imitate Anacreon! Mimesis, Poiesis and the Poetic Inspiration in the Carmina Anacreontea - Dümmler, Nicola; Baumbach, Manuel (Millennium-Studien / Millennium Studies, 2014)
Despite their rich tradition, the Carmina Anacreontea transmitted in the Palatine Anthology have received little scholarly attention. This neglect is linked to questions concerning their authenticity. Long read as poems by the ancient lyricist Anacreon, they are now regarded instead as imitations of Anacreontic lyricism. This volume presents the latest findings on the language, poetology, tradition, and reception of this lyrical collection.